AI-Powered Smart Water Distribution System: An Intelligent Approach for Resource Optimization - Surya Kiran Chebrolu; Kosuri Satya Srinivas (Utilitas Mathematica, 2025)
Water distribution systems face critical challenges including leakage detection, demand prediction, and optimization of resource allocation. This research presents a novel AI-powered smart water distribution system that integrates machine learning algorithms, IoT sensors, and cloud computing to revolutionize water management. The proposed system employs a hybrid approach combining deep learning for demand forecasting, reinforcement learning for valve control optimization, and anomaly detection algorithms for leak identification. Experimental results demonstrate significant improvements in water conservation (28%), operational cost reduction (32%), and leak detection accuracy (94.7%) compared to conventional systems. The framework's scalable architecture allows for seamless implementation across various urban water infrastructures, offering a sustainable solution to global water management challenges.